Chapter 1 Cowboys, Cod, Climate, and Conflict Navigations in the Digital Environmental Humanities - Travis, Charles (Taylor & Francis, 2023)
The DEH can be seen as an academic response to three major interwoven changes and challenges: the digital revolution; global warming and global warming and social-political agency related to environmental change. In the twenty-first century, we are challenged with a transformation in human collective intelligence. The key features of this transformation involve the "digital" replacing the "analogue"; design thinking and post-secularism supplanting tradition; and human agency emerging as the main driver of planetary change. Unlocking the keys to human perception, mitigating behavior and adaptive action may likely rank among the preeminent challenges we face in an age witnessing unprecedented rates of global change. The chapter showcases how the DEH is being applied by three international funded research projects: Larry McMurtry's Literary Geography; NorFish (Environmental History of the North Atlantic Fisheries, 1500-1800); and the Climates of Conflict in Babylonia project.